Retrospective analysis of clinical problems concerning acute pancreatitis in one treatment center - Kozieł, Dorota; Kozłowska, Monika; Deneka, Jan; Matykiewicz, Jarosław; Głuszek, Stanisław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Severe acute pancreatitis is still a difficult clinical problem, it is a challenge for medical teams, which should include the strategy of personalized medicine. In clinical observations, among patients with the fulminating course of acute pancreatitis developed during the first hours leading to irreversible multiorgan failure and death. Aim: To evaluate the frequency of occurrence and analyze the progression and treatment of severe acute pancreatitis (AP) in patients hospitalized during the years 2004–2010 at the Clinical Surgery Ward. Material and methods: One thousand and fifty patients treated for AP were included in the study; 97 patients with severe AP were subjected to a detailed clinical analysis. Results: The average age of the patients was 52.8 years. Relapses occurred in 14.9% of patients. The severe form of acute pancreatitis was diagnosed in 97 patients, which accounts for 9.2% of all the illnesses, and occurred significantly more often in male patients (p < 0.01). The most frequent etiological factors were cholelithiasis (46.4%), and idiopathic pancreatitis (27.8%); alcohol consumption was responsible for 22.7% of the cases; the occurrence of both a bile-derivative and alcoholic factor was found in 3.1% of the cases. A worsening clinical state resulted in laparotomy in 26 patients (26.8%), and re-laparotomy in 5 patients. Necrosectomy was performed on 15 patients, of whom 33.3% died due to complications. The total mortality in severe AP was 38.1%. The average age of the deceased was 66.5. Early deaths within 14 days were noted in 78.4% of patients (n = 29) who died due to severe AP. Conclusions : Severe AP in spite of implementing modern diagnosis and treatment methods is still associated with a high risk of death. Constant clinical observation and use of available prognostic scales are essential in improving AP prognoses.